Drinking water contamination potential and associated factors among households with under-five children in rural areas of Dessie Zuria District, Northeast Ethiopia - Gete Berihun; Masresha Abebe; Seada Hassen; Adinew Gizeyatu; Leykun Berhanu; Daniel Teshome; Zebader Walle; Belay Desye; Birhanu Sewunet; Awoke Keleb (Frontiers Media S.A., 2023)
ObjectiveMore than half of the 700 million people worldwide who lack access to a safe water supply live in sub-Saharan Africa, including Ethiopia. Globally, approximately 2 billion people use drinking water sources that are contaminated with fecal matter. However, little is known about the relationship between fecal coliforms and determinants in drinking water. Therefore, the objective of this study was to investigate the potential for contamination of drinking water and its associated factors in households with children under 5 years of age in Dessie Zuria district in northeastern Ethiopia.MethodsThe water laboratory was conducted based on the American Public Health Association guidelines for water and wastewater assessment using a membrane filtration technique. A structured and pre-tested questionnaire was used to identify factors associated with the potential for contamination of drinking water in 412 selected households. A binary logistic regression analysis was performed to determine the factors associated with the presence or absence of fecal coliforms in drinking water, with a 95% confidence interval (CI) and a value of p ≤ 0.05. The overall goodness of the model was tested using the Hosmer-Lemeshow test, and the model was fit.ResultsA total of 241 (58.5%) households relied on unimproved water supply sources. In addition, approximately two-thirds 272 (66.0%) of the household water samples were positive for fecal coliform bacteria. Water storage duration ≥3 days (AOR = 4.632; 95% CI: 1.529-14.034), dipping method of water withdrawal from a water storage tank (AOR = 4.377; 95% CI: 1.382-7.171), uncovered water storage tank at control (AOR = 5.700; 95% CI: 2.017-31.189), lack of home-based water treatment (AOR = 4.822; 95% CI: 1.730-13.442), and unsafe household liquid waste disposal methods (AOR = 3.066; 95% CI: 1.706-8.735) were factors significantly associated with the presence of fecal contamination in drinking water.ConclusionFecal contamination of water was high. The duration of water storage, the method of water withdrawal from the storage container, covering of the water storage container, the presence of home-based water treatment, and the method of liquid waste disposal were factors for fecal contamination in drinking water. Therefore, health professionals should continuously educate the public on proper water use and water quality assessment.